(untitled) (Praxis Educativa, 2012)
The development of the students teachinglearning process in higher education requires a harmonic conception that will allow students to give answers to the demands that society poses on university graduates. That is, to conform an integral human being, capable of carrying out different functions and tasks competitively in all the spheres of life. Didactics, the science whose object of study is the teaching-learning process, is characterized by a system of concepts, categories and laws which,combined, give direction and emphasize its development in order to achieve independent and creative professionals, fully committed to their social roles. With the objective of revealing these aspects, an analysis of the educational teaching process at university level is carried out following a holistic approach in the treatment of the fundamental didactic categories.